PRESCRIPTION TRENDS OF IMMUNOSUPPRESSANT DRUGS IN INDIAN RENAL TRANSPLANT PATIENTS (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The present study was conducted to find out the changes in immunosuppressant drug prescription pattern and trends in kidney transplant patients. In this study 613 Indian transplant patients who underwent kidney transplantation between July 2004 and June 2011 were enrolled. Various data of all transplant patients including immunosuppressant drug medication, changes in the prescription, use of antibody for induction and antirejection treatment were collected during their hospital stay and ambulatory visit. Antibody use as an induction agent has increased from during the study period. Induction was used in 23.1% during the year 2005 and increased to 44.4% during the year 2009. Among induction agent ATG was most commonly preferred agent, followed by daclizumab and basiliximab (24% ATG Vs 6.9% daclizumab Vs 6.9% basiliximab). Use of tacrolimus has increased (94% on tacrolimus vs 6% on cyclosporine in 2010). Mycophenolate mofetil is most commonly used antiproliferative agent (80% on MMF vs 20% on azathioprine in 2010). Trend is towards more use of MMF though azathioprine is being used in significant number of patients. Analysis of maintenance immunosuppression after renal transplant showed 60% patient maintained their original regimen over 7 years of follow up. Sirolimus was introduced in 1.5 to 7% patients during follow up period. Anti rejection treatment was required in 22-47% renal transplant recipients and trend towards decreasing rejection episode was seen. Steroids were used in the treatment of rejection in 90-100% patients. Use of ATG for treatment of rejection has increased from 11.5% in 2005 to 40% in 2010-11. By this study we conclude that immunosuppressant drugs have passed through significant changes during the year 2005 to 2011. Use of ATG as an induction agent and for treatment of rejection has increased. Similarly MMF and tacrolimus are most commonly used in maintenance regimen for renal transplant patients.